2017
DOI: 10.1177/1010428317706229
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CASC2 regulates cell biological behaviour through the MAPK signalling pathway in hepatocellular carcinoma

Abstract: Long non-coding RNAs have previously been demonstrated to play important roles in regulating human diseases, especially cancer. However, the biological functions and molecular mechanisms of long non-coding RNAs in hepatocellular carcinoma have not been extensively studied. The long non-coding RNA CASC2 (cancer susceptibility candidate 2) has been characterised as a tumour suppressor in endometrial cancer and gliomas. However, the role and function of CASC2 in hepatocellular carcinoma remain unknown. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…The data suggested that these lncRNAs may participate in the tumorigenesis and development via regulating the cancer-related pathways in TNBC. Our data are in line with previous reports and provide a new therapeutic possibility for TNBC [45,46], but further experimental validation is needed .…”
Section: Discussionsupporting
confidence: 81%
“…The data suggested that these lncRNAs may participate in the tumorigenesis and development via regulating the cancer-related pathways in TNBC. Our data are in line with previous reports and provide a new therapeutic possibility for TNBC [45,46], but further experimental validation is needed .…”
Section: Discussionsupporting
confidence: 81%
“…Cancer susceptibility candidate 2 (CASC2) is a lncRNA located on chromosome 10q26 that was discovered by Baldinu et al () in the context of endometrial cancer. It has since been shown to play a role in regulating the progression and growth of a number of cancers, including colorectal (Huang et al, ), lung (He et al, ), and hepatocellular (Gan et al, ), among others (Baldinu et al, ; Cao et al, ; Li, Xue, Feng, & Mao, ; Wang et al, ). CASC2 acts through microRNAs (miRNAs) (Huang et al, ; Wang et al, ), as well as through the Wnt/β‐catenin (Pei et al, ), MAPK (Gan et al, ; Li et al, ), and NF‐κB signaling pathways (Ni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has since been shown to play a role in regulating the progression and growth of a number of cancers, including colorectal (Huang et al, ), lung (He et al, ), and hepatocellular (Gan et al, ), among others (Baldinu et al, ; Cao et al, ; Li, Xue, Feng, & Mao, ; Wang et al, ). CASC2 acts through microRNAs (miRNAs) (Huang et al, ; Wang et al, ), as well as through the Wnt/β‐catenin (Pei et al, ), MAPK (Gan et al, ; Li et al, ), and NF‐κB signaling pathways (Ni et al, ). Even though recent research (Gan et al, ) has suggested a mechanism for CASC2 activity in HCC, characterizing the effects of CASC2 on HCC growth and progression with even greater specificity promises to improve our HCC treatment capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in esophageal carcinoma, CASC2 was shown to be an oncogene suppressor through inhibition of the NF-κB pathway [29] or that it acted as a ceRNA of miR-18a-5p to exert its biological effects by modulating the expression of PTEN [30]. In hepatocellular carcinoma, lncRNA CASC2 may regulate cell biological behavior through the MAPK signaling pathway [17]. Additionally, it suppressed the epithelial-mesenchymal transition of hepatocellular carcinoma cells through the CASC2/ miR-367/FBXW7 axis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Now increasing numbers of studies have shown that CASC2 is also significantly downregulated in other cancers, such as hepatocellular carcinoma, colorectal cancer, and bladder cancer [17-19], and it could act as a tumor suppressor with implications for diagnosis and therapy [20]. Numerous researchers have reported that CASC2 is implicated in tumor initiation and progression and has shown a potential for predicting cancer prognosis [21-23].…”
Section: Introductionmentioning
confidence: 99%